Challenges in Implementing Maritime Development in Indonesia: From Concept to Reality - Fera Kasmita; Elisabet Desiana; Roberta Bela (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2026)
Indonesia’s maritime development has been positioned as a strategic national agenda due to its archipelagic geography, abundant marine resources, and strategic location within regional and global sea lanes. However, the implementation of maritime development continues to face a gap between policy concepts and practical realities, particularly in governance coordination, port connectivity, logistics efficiency, digital transformation, environmental sustainability, and coastal community inclusion. This study aims to examine the main challenges in implementing maritime development in Indonesia and to explain how an adaptive and integrated governance framework can support the transformation of maritime policy into concrete development outcomes. This research employs a qualitative descriptive-analytical approach using secondary data collected through literature review and document analysis. The data were analyzed through qualitative content analysis by identifying key themes related to maritime governance, port logistics, blue economy implementation, institutional reform, and regional development. The findings show that Indonesia’s maritime development is constrained by fragmented institutional arrangements, uneven port infrastructure, high logistics costs, weak hinterland integration, limited digital interoperability, and insufficient environmental safeguards. The study also finds that maritime development requires stronger coordination among central government, regional governments, port authorities, private sector actors, universities, civil society, and coastal communities. In conclusion, Indonesia’s maritime development should move beyond infrastructure-oriented policies toward adaptive, collaborative, and sustainability-based governance. Strengthening institutional integration, digital readiness, green port practices, regional participation, and blue economy implementation is essential to transform Indonesia’s maritime vision from a policy concept into an inclusive and sustainable development reality.